Research on Path Planning for Tetrahedral Robots Based on A* Algorithm - Wang Yubin; Shen Zhenjun; Wang Yuchen; Chen Dongdong (Jixie chuandong)
To solve the problem of obstacle avoidance and path planning of tetrahedral tumbling robots in the triangular grid map, a path planning method based on the A* algorithm for tetrahedral tumbling robots is proposed. Based on the robot motion principle, it is analyzed that the motion trajectory of the robot is the triangular grid. The robot position and orientation representation method is proposed with the triangular grid map, and then the robot path planning method based on the A* algorithm is proposed. Matlab software is used to simulate and calculate the path planning process of the tetrahedral robot, which verifies the feasibility and correctness of the proposed method. It has laid an important foundation for robotic land exploration in deep space patrol.